АНАЛИЗА НА МОЖНОСТА ЗА ВОВЕДУВАЊЕ НА ДРУШТВО СО ОГРАНИЧЕНА ОДГОВОРНОСТ СО ЕДНО ЕВРО ОСНОВНА ГЛАВНИНА ВРЗ ОСНОВА НА ГЕРМАНСКИОТ МОДЕЛ - Goran Koevski, Borka Tushevska, Darko Spasevski (Правен факултет, Универзитет „Гоце Делчев“ – Штип, 2020)
Within the paper, the authors are making analysis of the newly proposed amendments to the Law on Commercial Companies regarding the introduction of the possibility of establishing a limited liability company with a minimum paid-in capital of one euro. The authors refer to the German solution, which in 2008 also introduced the possibility of establishing a limited liability company with a minimum paid-in capital of one euro. This solution was later included in Croatia too. All of these trends are motivated by the British decision to establish a company with a share capital of one pound.
Keywords: paid-in capital, limited liability company, reform of company law